Anne of Green Gables - West, Clare; Montgomery, L. M. 1874-1942.; Simpson, Kate. (Oxford : Oxford University Press, 2000)
Anne, an eleven-year-old orphan, is sent by mistake to live with a lonely, middle-aged brother and sister on a Prince Edward Island farm and proceeds to make an indelible impression on everyone around her.
English language and literature.
Keywords: Orphans -- Fiction; Friendship -- Fiction; Islands -- Fiction; Country life -- Prince Edward Island -- Fiction; Prince Edward Island -- History -- 20th century -- Fiction; Canada -- History -- 1867-1914 -- Fiction